Satisfacción laboral en el Servicio de Rayos X de una Institución Privada de Salud de Lima, Nivel III-2, 2015 - Román Meza, Alexander H. (2015)
Objective: To describe job satisfaction in the X-Ray Department of a level III-2 private ]health institution in Lima, in 2015. Material and Methods: The present study is quantitative, descriptive, prospective and cross-sectional. He population was of 22 people, the sample included everyone in the population.  The unit of analysis was the Medical Technologists of Radiology. The job satisfaction was evaluated by the "Job Satisfaction Questionnaire S10 / 12" by Melia JL and Peiró JM. Results: Of the total population, 77.3% were hired on a fixed term and 40.9% had been working for 12 months or more.86.4% of participants were occupationally satisfied. 65.9% expressed satisfaction with the services received dimension, and 10.2%had an indifferent satisfaction with the physical environment dimension. Conclusion: Job satisfaction was high in the department but in the analysis, it was determined that the physical environment is where the institution must improve, compared to the benefits received and supervision.